Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1258/004947507779951961
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in HIV post-exposure prophylaxis for occupational injuries in a large teaching hospital in Malawi

Abstract: We describe the evaluation of the HIV post-exposure prophylaxis (PEP) programme for occupational injuries in Queen Elizabeth Central Hospital, Blantyre, Malawi. An audit was performed 1 year after introduction, by reviewing files of all clients who sought advice regarding PEP. In addition, the incidence of occupational injuries and awareness of the programme were assessed through interviews with nurses. The logistics of the programme were adequate. Of 29 clients who reported occupational injuries,19 started PE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 4 publications
3
10
0
Order By: Relevance
“…One survey in Malawi suggested that half of nurses had a needle stick injury within the previous year. 25 This rate is similar to rates in resource-rich settings prior to the widespread adoption of engineered needle-safe solutions. 26 The consequences of outdated needle practices combined with high prevalence rates of HIV, hepatitis B and hepatitis C may be catastrophic.…”
Section: Discussionsupporting
confidence: 52%
“…One survey in Malawi suggested that half of nurses had a needle stick injury within the previous year. 25 This rate is similar to rates in resource-rich settings prior to the widespread adoption of engineered needle-safe solutions. 26 The consequences of outdated needle practices combined with high prevalence rates of HIV, hepatitis B and hepatitis C may be catastrophic.…”
Section: Discussionsupporting
confidence: 52%
“…A striking finding of the study is the extent to which health workers test after occupational exposure, which underscores the importance of guidelines, practices and resources designed to protect health workers and provide post-exposure prophylaxis. With the persistence of moral judgements which promote stigma about HIV and sexual contract, it is possible that health workers may find it easier to seek an HIV test after occupational exposure, despite evidence from Malawi showing that access to post exposure prophylaxis is low (Van Oosterhout et al, 2007). The other commonly reported reason for testing – ill health – underscores health workers’ vulnerability and the fact that even they sometimes delay testing until they experience symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Kenya found that only 4% of HCWs accessed PEP following needle stick injuries [12]. Fear of disclosure and reluctance to test may be major obstacles to HCWs access to HIV testing and counseling (HTC) and other related services [13, 14]. Being infected with HIV can be a source of personal and professional shame for a health worker, and may also invoke fear of losing one's job and damaging future career prospects [14–16].…”
Section: Introductionmentioning
confidence: 99%